2022
DOI: 10.7717/peerj.13350
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenolic extract from Punica granatum peel causes cytoskeleton-related damage on Giardia lamblia trophozoites in vitro

Abstract: Background Diarrheal diseases caused by protozoa have a great impact on human health around the world. Giardia lamblia is one of the most common flagellates in the intestinal tract. Factors such as adverse effects to first-line drugs or the appearance of drug-resistant strains, make it necessary to identify new treatment alternatives. Agroindustry waste, like pomegranate peel, are a source of phenolic compounds, which possess antiparasitic activities. In vivo studies demonstrated antigiardiasic potential by re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…These authors mention that this extract inhibits the growth and decreases the adhesion of trophozoites by 74.36% and 46.8%, respectively, in trophozoites treated with 200 μg/mL. They also report an IC 50 of 179 μg/mL, highlighting alterations in the tubulin gene’s expression and the distribution of this protein within the cell [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors mention that this extract inhibits the growth and decreases the adhesion of trophozoites by 74.36% and 46.8%, respectively, in trophozoites treated with 200 μg/mL. They also report an IC 50 of 179 μg/mL, highlighting alterations in the tubulin gene’s expression and the distribution of this protein within the cell [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been confirmed that this extract possesses inhibitory properties that affect the growth of G. lamblia trophozoites and, in addition, diminish the parasite’s ability to adhere to the inner wall of the duodenum. Furthermore, it is important to note that the authors report modifications in tubulin gene expression and its intracellular localization [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cells treated with DMSO (the negative control) or terfenadine (1, 2, 3 μM) cells were harvested after 48 h and processed to obtain a total protein extract according to an earlier report [ 54 ]. Briefly, the parasites were collected by cooling and posterior centrifugation at 1973× g for 10 min at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…SDS-PAGE and Western Blot Assay 4.9.1. Protein Extracts and SDS-PAGE Cells treated with DMSO (the negative control) or terfenadine (1, 2, 3 µM) cells were harvested after 48 h and processed to obtain a total protein extract according to an earlier report [54]. Briefly, the parasites were collected by cooling and posterior centrifugation at 1973× g for 10 min at 4 • C. The cells were lysed with RIPA buffer (sodium chloride, 150 mM, Tris-HCL, 50 mM, Nonidet P-40 1%, sodium deoxycholate 0.5%, SDS 0.1%) supplemented with complete protease inhibitor (Roche), PMSF (Sigma-Aldrich St. Louis, MO, USA), and sodium orthovanadate (Sigma-Aldrich St. Louis, MO, USA) and were incubated on ice for 30 min.…”
Section: Immunofluorescencementioning
confidence: 99%
“…One comprehensive analysis focused on a polyphenolic extract derived from Punica granatum peel, which induced cytoskeletal changes in Giardia trophozoites. Within the extract, ellagitannins, flavones, and ellagic acid exhibited inhibitory effects on cell growth and adhesion [ 114 ]. Moreover, the extract altered the expression and distribution of alpha-tubulin in trophozoites, as confirmed via Western blot and immunofluorescence microscopy.…”
Section: New Compoundsmentioning
confidence: 99%